2004
DOI: 10.1002/app.20462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal conductivity and heat transfer on crystallization, structure, and morphology of polypropylene containing different fillers

Abstract: ABSTRACT:The crystallization behavior, structure, and morphology developed was investigated for polypropylene containing different fillers such as silica, calcium carbonate, talc, mica, graphite, etc. by using compression-molded samples prepared at several cooling rates. It was observed that the crystallinity obtained for any given composition depended on the thermal conductivity of the filler and the PP composite containing it as well as the cooling rate to which it was subjected. These composites exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…It is known that the crystal structure of the matrix has a key role in determining the properties of polymer-based composites (Tchmutin et al 2003;Radhakrishnan et al 2004). The XRD characterizations of nano-ATO (curve a), the pure PAN (curve d) and the PAN/ATO nanocomposites with 4 and 8 wt% of nano-ATO contents (curves b and c) were conducted (see figure 6).…”
Section: Wide-angle X-ray Diffraction Studymentioning
confidence: 99%
“…It is known that the crystal structure of the matrix has a key role in determining the properties of polymer-based composites (Tchmutin et al 2003;Radhakrishnan et al 2004). The XRD characterizations of nano-ATO (curve a), the pure PAN (curve d) and the PAN/ATO nanocomposites with 4 and 8 wt% of nano-ATO contents (curves b and c) were conducted (see figure 6).…”
Section: Wide-angle X-ray Diffraction Studymentioning
confidence: 99%
“…Radhakrishnan et al [17] reported on the relationship between the thermal conductivity of different types of fillers (silica, glass fibre, mica, talc, etc.) on the preferential orientation of the PP chains.…”
Section: Morphologymentioning
confidence: 99%
“…19 Thermal properties have been improved by tens of degrees Celsius with the inclusion of low volume fractions of nanoparticles. [19][20][21][22][23][24] Given these multifunctional characteristics as well as improved mechanical properties, polymer nanocomposites have many existing and potential applications in the aerospace, automobile, and electronics industries.…”
Section: Introductionmentioning
confidence: 99%